Cumulative Signaling Through NOD-2 and TLR-4 Eliminates the Mycobacterium Tuberculosis Concealed Inside the Mesenchymal Stem Cells - Aqdas, Mohammad; Singh, Sanpreet; Amir, Mohammed; Maurya, Sudeep Kumar; Pahari, Susanta; Agrewala, Javed Naim (Frontiers in Cellular and Infection Microbiology, 2021)
Since long, tuberculosis (TB) has been inflicting mankind with highest morbidity and mortality. Although, the current treatment is extremely potent, yet few bacilli can still hide inside the host mesenchymal stem cells (MSC). Functional capabilities of MSCs are known to be modulated by TLRs, NOD-2 and RIG-1 signaling. Therefore, we hypothesize that modulating the MSC activity through TLR-4 and NOD-2 can be an attractive immunotherapeutic strategy against Mtb. In our current study, we observed that MSC stimulated through TLR-4 and NOD-2 (N2.T4) i) activated MSC and augmented the secretion of pro-inflammatory cytokines; ii) co-localized Mtb¬ in the lysosomes; iii) induced autophagy; iv) enhanced NF-κB activity via p38 MAPK signaling pathway; v) significantly reduced the intracellular Mtb¬ survival. Overall, the results suggest that the triggering through N2.T4 can be a future immunotherapy to eliminate the Mtb¬ concealed inside the MSC.